2011
DOI: 10.1007/s00784-011-0577-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between maxillofacial radiographic features and systemic severity as sickle cell disease severity predictor

Abstract: This study was conducted to investigate the relationship among radiographic features observed on panoramic radiographs of sickle cell disease patients and analyze their relationship with history of systemic severity of the disease. Panoramic radiographs of 71 subjects with sickle cell disease were evaluated for the presence of the following radiographic bony alterations: radiopaque areas, increased spacing of bony trabeculae, horizontal arrangement of bony trabeculae and corticalization of mandibular canal. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
0
8
0
2
Order By: Relevance
“…In evaluating 71 patients with SCA, Neves et al. () found statistically significant associations between history of clinical jaundice and increased trabecular spacing ( p = .02) and between a history of stroke and a horizontal pattern of trabecular bone ( p = .04). These findings demonstrate the importance of studies on the oral complications of the disease as predictors of systemic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In evaluating 71 patients with SCA, Neves et al. () found statistically significant associations between history of clinical jaundice and increased trabecular spacing ( p = .02) and between a history of stroke and a horizontal pattern of trabecular bone ( p = .04). These findings demonstrate the importance of studies on the oral complications of the disease as predictors of systemic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…SCA and SCT subjects have higher frequencies of trabecular bone changes. Some studies usually report that some radiographic features of SCA are increased radiolucency of the jaws due to the decreased number of trabeculae, coarse trabeculae pattern and step‐ladder appearance created in the interdental alveolar bone by horizontal rows of trabeculation (da Fonseca et al., ; Neves et al., ), but only two studies reported theses changes in SCT subjects (Gillis & West, ; Halstead, ). The presence of these radiographic features can be deterministic for the existence of SCA and SCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En el análisis radiográfico se hallaron cambios óseos primarios en la zona interradicular de incisivos inferiores anteriores y un patrón de escalera molar inferior izquierdo con mayor notoriedad, los cuales son consistentes con lo reportado en estudios de radiografías panorámicas en pacientes con ACF (23).…”
Section: Discussionunclassified